Solving vehicle routing problem by using ant colony optimization case study in jiaranai drinking water company - Srisuwandee, Thitinon; Pitakaso, Rapeepan (Asia-Pacific Journal of Science and Technology, 2017)
The organizations which use transportations for their main activity like the case study of Jiaranai drinking water company amphur Warinchamrap Ubonratchathani province. It is very important that needs the appropriate management of transportation to meet the needs for their customers, the satisfactions of services, and decreasing budgets. So, researcher designs and implements algorithm which using the application of Ant Colony Optimization (ACO) and improve the solution using Crossover-Move, 2-Opt, and One-Move heuristics to solve vehicle routing problem (VRP) in this case. The capacity of vehicle is limited and each customer has uncertain demand so we figure this problem by using mode and statistical average. The VRP has been known as an NP-hard problem. The experimental results compared to the current vehicle routes show that the proposed ACO with Crossover-Move, 2-Opt, and One-Move heuristics provides good solutions. The total distance can be reduced from 584.25 kilometers to 441.35 kilometers or decreased by 24.46%.